Service quality perception and customer satisfaction in Islamic banks of Pakistan: the modified SERVQUAL model - Ali, Muhammad; Ali Raza, Syed (Routledge, 2017)
The aim of this study is to measure the relationship between service quality and customer satisfaction among the customers of Pakistani Islamic banks. This study employed a modified SERVQUAL model by introducing a unique dimension of compliance in the context of service industry. A self-administered questionnaire-based field survey was conducted with the help of modified SERVQUAL dimensions. Data were gathered from 450 walk-in customers of Islamic bank. The sample data were statistically analysed through exploratory factor analysis followed by confirmatory factor analysis (CFA) and structural equation modelling (SEM) analysis to determine the service quality perception and customer satisfaction. Namely, CFA is used in order to test the model validity, while SEM is used for testing the impact of different service quality dimensions on customer satisfaction. Results revealed that the multidimensional service quality scale is positively and significantly associated with the unidimensional scale of customer satisfaction. In addition, the compliance dimension of the SERVQUAL model proved its importance by showing the highest contributing factor in the overall model. Furthermore, this study has practical implications for the policy-makers of Islamic banks to better understand the behavioural intentions of Islamic bank customers.